Through the telescope : - Barnes-Svarney, Patricia L. (McGraw Hill, 2000)
Through the Telescope presents a uniquely "user-friendly" view of the universe, and offers both novice and advanced amateur astronomers some of the best tools available to watch the nighttime skies. You'll learn all about: Setting up a good, user-friendly telescope system; Spotting comets and asteroids; Upgrading your telescope for peak performance; How to spot star clusters, nebulae, even a supernova; Forming your own network of amateur astronomers.